MARKETING ‘LITERARY ENGLAND’ TO THE US TRAVELLER - Themistocleous, Christos; Ingram, Claire; Rickly, Jillian M.; McCabe, Scott (My University, 2019)
This paper examines English literary tourism through the eyes of the bibliophile and non- bibliophile. It adopts an inductive between-subjects experimental design to investigate the likelihood of a general sample of the US population visiting literary attractions compared to that of US literary society members. The findings suggest that literary society members are aware of English literary destinations and are likely to visit these sites independently regardless of prior knowledge of the associated literary work. Non-members – once made aware of destinations – will also visit independently but demonstrate greater tendency to do so if they’ve read or watched the related book or film. By understanding the stimuli driving each group to engage (or not) in literary tourism, this paper gives rise to important implications for how the tourism industry can better market ‘Literary England’ to different segments so as to best capitalise on the US outbound market.
Keywords: Literary Tourism; Marketing Tourism; Travel studies; Tourist behaviour